"Scorpionate-like" complexes that are held together by hydrogen bonds: Crystallographic and spectroscopic studies of (3-NH(t-butyl)-5-methyl-pyrazole)nMX2 (M = Zn, Ni, Co, Mn; n = 3, 4; X = Cl, Br). (16th August 2016) - Serpas, Lee; Baum, Robert R.; McGhee, Alyssa; Nieto, Ismael; Jernigan, Katherine L.; Zeller, Matthias; Ferrence, Gregory M.; Tierney, David L.; Papish, Elizabeth T.
Graphical abstract: Amino-substituted pyrazole ligands form 3:1 and 4:1 transition metal complexes with zinc(II), cobalt(II), manganese(II), and nickel(II). These complexes exhibit hydrogen bonds between NH groups and halide ions. Thus these are "scorpionate-like" metal complexes that are held together by hydrogen bonds rather than covalent bonds. Abstract: The hydrogen bonding ligand, 3-NH(t-butyl)-5-methyl-pyrazole, forms "scorpionate-like" first row transition metal complexes that are held together by hydrogen bonds rather than covalent bonds. The formulae of these complexes are (LH) n MX2, where n = 3, 4; X = Cl, Br; and LH = 3-NH(t-butyl)-5-methyl-pyrazole. The amino-substituted pyrazole can hydrogen bond via both the amino group and the pyrazole NH to form intramolecular NH to halide hydrogen bonds. These complexes have been well characterized and show a 3:1 ratio of ligand to metal for zinc and cobalt (1 and2 ), and a 4:1 ratio of ligand to metal for manganese and nickel (3 and4 ). The hydrogen bonding interactions appear to be stronger for the 3:1 complexes. The crystallographic and spectroscopic studies (EPR and NMR) have shown that these hydrogen-bonding interactions are strong enough to perturb metal halogen bond distances and, with non-hydrogen bonding solvents, the hydrogen bonds appear to hold these complexes together in solution.